2007
DOI: 10.1111/j.1360-0443.2006.01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Attentional re‐training decreases attentional bias in heavy drinkers without generalization

Abstract: Although heavy drinkers can learn to attend selectively to an alternative category for alcohol, a single AR is not sufficient to decrease symptoms of problem drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
173
2
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(195 citation statements)
references
References 42 publications
16
173
2
4
Order By: Relevance
“…This suggests that active working memory representations cannot fully override long-term alterations of the attentional set when a featurespecific form of Feature Search Mode has been adopted. This also offers as explanation of the sustainability of attentional biases in the addiction literature (Schoenmakers et al, 2007;Field et al, 2007). Addicts may be trapped in a situation where their attentional control settings are permanently cued towards a feature-specific Feature Search Mode that selects items via long-term memory representations (Janes et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that active working memory representations cannot fully override long-term alterations of the attentional set when a featurespecific form of Feature Search Mode has been adopted. This also offers as explanation of the sustainability of attentional biases in the addiction literature (Schoenmakers et al, 2007;Field et al, 2007). Addicts may be trapped in a situation where their attentional control settings are permanently cued towards a feature-specific Feature Search Mode that selects items via long-term memory representations (Janes et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported that an experimental increase in attentional bias led to increased subjective craving (Field and Eastwood 2005; Field et al 2007a) and drinking (Field and Eastwood 2005). However, an experimental decrease in attentional bias has not been found to decrease craving or drinking behavior (Field et al 2007a;Schoenmakers et al 2007). In sum, there is ample evidence for the interrelation of attentional bias, approach bias, and craving, but it is not clear under which conditions these relations are manifested.…”
mentioning
confidence: 99%
“…10 In the other study, AB in the avoid group decreased when compared with the control group at SOA 500 ms, but not at 200 ms, and generalized to new stimuli, but did not correlate with craving. 53 The latter had the largest number of trials in this category, and although the AB did not correlate with craving, the participants in the avoid group took longer to relapse and were discharged earlier than those in the control group.…”
Section: Anxietymentioning
confidence: 73%
“…51 In contrast, of the five studies that compared avoid (to drug) and control groups, only one found no differences between groups. 52 The two studies about alcohol use 10,53 found differences between groups in the post-test. In one of all participants showed an attentional bias toward unhealthy food cues at baseline.…”
Section: Drug Addictionmentioning
confidence: 99%
See 1 more Smart Citation